2017
DOI: 10.25115/ejrep.v9i25.1470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of teaching of self-regulated learning strategies on attribution styles in students

Abstract: Introduction. Nowadays, self-regulated learning has become an important focus in research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…The results of the current study demonstrated that SRSD is found to be effective on writing persuasive essay for (AFL) students in general, in accordance with the previous studies (Ghanizadeh, 2012;Tavakolizadeh, & Qavam, 2011;Cleary, & Zimmerman, 2004;Kitsantas, Winsler, Huie, 2008;Duckworth, Akerman, MacGregor, Salter, & Vorhaus, 2009). A practical clarification for these findings is that having received training of self-regulated strategies, such as modeling, graphic organizer, mnemonics, self-directions, and self evaluation, increase self efficacy, and self management; because writers engaged in their learning as they know what to do to perform a task, visualize the argument, state the goal, and manipulate their learning environments to meet their needs, which seems to have an impact on enhancing the effort and perseverance during the task of writing, and help student concentrate on content, structure, and other comprehensive factors.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the current study demonstrated that SRSD is found to be effective on writing persuasive essay for (AFL) students in general, in accordance with the previous studies (Ghanizadeh, 2012;Tavakolizadeh, & Qavam, 2011;Cleary, & Zimmerman, 2004;Kitsantas, Winsler, Huie, 2008;Duckworth, Akerman, MacGregor, Salter, & Vorhaus, 2009). A practical clarification for these findings is that having received training of self-regulated strategies, such as modeling, graphic organizer, mnemonics, self-directions, and self evaluation, increase self efficacy, and self management; because writers engaged in their learning as they know what to do to perform a task, visualize the argument, state the goal, and manipulate their learning environments to meet their needs, which seems to have an impact on enhancing the effort and perseverance during the task of writing, and help student concentrate on content, structure, and other comprehensive factors.…”
Section: Resultssupporting
confidence: 93%
“…, University learners (Ghanizadeh, 2012;Tavakolizadeh, Qavam, S. E, 2011;Cleary, Zimmerman, 2004;Kitsantas, Winsler, Huie, 2008;& Duckworth, Akerman, MacGregor, Salter & Vorhaus, J., 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Various different studies have evidenced the relationship between self-regulation and different behavorial problems, both internalized and externalized. In this vein, a lack of self-regulation has been related to anxiety, depression, aggressive conduct, bullying, and delinquency ( Muris et al, 1999 ; Beauchaine et al, 2007 ; de la Fuente et al, 2009 ; Brooks et al, 2010 ; Garner and Hinton, 2010 ; Tavakolizadeh and Ebrahimi-Qavam, 2011 ; Rhodes et al, 2013 ; White et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Students operating from uncontrolled motivations tend to execute more effective strategies, such as management, concentration, and self-testing (Wijnia, Loyena, & Derous, 2011). Focusing more on the student’s expectations and values reduces several problems caused by controlled motivation and content-driven education, including the maintenance of gender disparities in academic subjects, decreased motivation, learned helplessness, reduced productivity, maladaptive social behaviors, self-handicapping, and undermined learning (Bandura & Schunk, 1981; Butler, 2006; Chen, Wu, Kee, Lin, & Shui, 2009; Lüftenegger et al, 2012; Oortvliet & Darnon, 2010; Tavakolizadeh & Qavam, 2011).…”
Section: Principles That Support the Eight Components Of H2o-centered Educationmentioning
confidence: 99%